The roots of regional trust - Christoph Hauser; Gottfried Tappeiner; Janette Walde (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
Social trust is increasingly seen as an important determinant of economic growth and social prosperity in regions and nations. Even in a comparatively homogeneous area such as Europe, there are stark sub-national differences in levels of generalized trust. It is thus of crucial importance to identify the driving forces of regional trust and analyze the dynamics of its formation. The present paper considers these issues based on three waves of the European Values Study. Evidence is provided to demonstrate that values of regional trust remain substantially stable over an approx. 20-year period and are modified only through spatially correlated random noise processes. This finding is consistent with additional analyses identifying slow-moving factors that are responsible for the spatial distribution of trust scores and are buried deep in the cultural background of a society. Hence, in spite of its economic significance, social trust does not appear to be amenable to political intervention in the short to medium term.
Keywords: C21; R10; Z13; 330; social capital; European regions; spatial econometrics